Concordance of patients' beliefs about chronic obstructive pulmonary disease, their comorbidities, and their medications. Issue 4 (April 2020) - McInerney, Grace E.; Muellers, Kimberly; O'Conor, Rachel; Wolf, Michael S.; Leventhal, Howard; Wisnivesky, Juan P.; Federman, Alex D.
Highlights: Illness beliefs among patients with multimorbidity are associated. Patients with multimorbidity have associated beliefs about medications. Concern about illness and impact of illness on emotion were most associated domains. Abstract: Objective: To test the association of chronic obstructive pulmonary disease (COPD) illness and medication beliefs with those specific to hypertension or diabetes in patients with COPD and coexisting chronic conditions. Methods: A cross-sectional analysis of data collected from a sample of 282 adults with COPD and comorbid hypertension or diabetes recruited from primary care practices in New York, NY, and Chicago, IL. Beliefs about COPD, hypertension, and diabetes were measured using the Brief Illness Perception Questionnaire. Higher scores indicate a more adaptive view of the illness. Beliefs about medications were measured using the 10-item Beliefs about Medicines Questionnaire; higher scores on the two subscales indicate increased concerns and necessity, respectively. Results: In adjusted analyses, scores for COPD and hypertension as well as COPD and diabetes illness beliefs, medication necessity, and medication concern were significantly associated. Conclusion: Patients with COPD and comorbid hypertension or diabetes have consistent beliefs about their diseases and the medications used to treat them. Practice implications: : The consistency of beliefs across conditions may help in the development of a more holistic approach to disease management in patients with COPD who have comorbid illnesses and contribute to a better understanding of the Common-Sense Model of Illness Representation.